Land Acquisition for Public Interests: A Review from the Human Rights Context - Yesi Nurmantiyas Sari; Rizal Nugroho; Al Khanif (Indonesian Journal of Law and Society, 2020)
Land acquisition for public purposes is an activity intended for the public interest that uses community land. To be able to carry out development in the public interest, the government uses state land. If state land is not sufficient or cannot maximize development, the government can use land from individuals or groups by carrying out the land acquisition. In implementing land acquisition, the land acquisition team must pay attention to the rights of the people affected by land acquisition. Irregularities that often occur in the implementation of land acquisition are related to discrimination, intimidation, and violence. These rights are included in human rights, which must be upheld and protected because this is closely related to property rights. Human rights give an understanding that the right to own something is the right of every citizen, including the right to own land is one of the human rights inherent in each person per person in groups. While property rights must not be taken arbitrarily and against the law, such matters are regulated in Article 28H of the 1945 Constitution. This paper concludes that the construction activities of the New Yogyakarta International Airport (NYIA) carried out violated human rights; this is because the land acquisition team has committed violence, discrimination, and violence against the people affected by land acquisition. The form of legal protection provided by the government is proper compensation.